(3GdJPgjH aj TQM GdJgPjHs - (3GdNHjUj, aNQ GdOjf, YHjO Gddg Hf aVd Gddg, J (B1050 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; Ef CMb eG jJRjf HfTQg efWb GdeGVj hGdMGVQ MeO Gddg Ld LdGdg Ydi GdBjI GdeRgQI GdQjGV hHYO ajbhd YHjO Gddg Hf aVd Gddg GdNHjUj deG QCjJ GdeNJUQ GdeSei HGdJgPjH GdefShH Edi GdJaJGRGfj SejJg HGdJPgjH s
(3BNQgG (B:s
(3hHjGf GdMGLI Edjg Cj HjGf efaYJg hYQVg hehVhYg hbO YQaJ cd hGMO ef gPg aj UOQ GdcJGH adG jajOg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4/196s
(3cTa GdXfhf (B1/516s
(3gOjI GdYGQajf (B1/650s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdadSaI hGdefWbs